Inspiring and Inspired Instructional Interactions through Children Poetry - Solis - Setiyani (Journal of English Language Studies, 2019)
EFL young learners just made a little interaction with children poetry since the teachers seemed never use it as a learning material for them. The study intended to explore the instructional interactions occurred in the classroom by making use of children poetry as the learning material. It is an exploratory study which joined seven sixth graders from two elementary schools in Bandung of the age 11 to 12 years old as the research participants. The researcher used several techniques to obtain the data namely non-participant observations, video recording, document collection, and in-depth interviews. The data analysis was descriptive. Three way interactions were observed in the class, namely students-teacher interaction, student-student interaction, and student-text interaction. By playing appropriate teacher’s role, designing effective classroom activities, and selecting suitable children poetry, EFL young learners can be inspired and inspiring in the instructional interactions.